2005
DOI: 10.1007/s00432-005-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tumor cell dissemination in pancreatic ductal carcinoma patients by CK 20 RT-PCR indicates poor survival

Abstract: Disseminated tumor cells can be detected in patients with pancreatic ductal adenocarcinoma by CK 20 RT-PCR. Detection rates are stage dependent, and survival analysis demonstrated statistically relevant data. From a clinical point of view, this finding is especially noteworthy for the group of well- and moderately-differentiated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 25 publications
6
76
2
3
Order By: Relevance
“…Khoja et al (2012) compared CellSearch and ISET in terms of CTC detection in 54 patients with pancreatic cancer, and found that ISET detects a higher number of CTCs than the CellSearch System. Polymerase chain reaction (PCR)‐based methods are also commonly used; CTCs were detected in 33.8–84% of patients by using Nested PCR with CK20 mRNA as a CTC marker in different studies (Soeth et al, 2005; Zhou et al, 2011). The method of combined immunostaining for CD45, DAPI, and CEP8‐FISH has shown great potential for CTC detection; this method yielded sensitivities of 83.33% and 76.25% for detecting CTCs in lung and ovarian cancers, respectively (Ning et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khoja et al (2012) compared CellSearch and ISET in terms of CTC detection in 54 patients with pancreatic cancer, and found that ISET detects a higher number of CTCs than the CellSearch System. Polymerase chain reaction (PCR)‐based methods are also commonly used; CTCs were detected in 33.8–84% of patients by using Nested PCR with CK20 mRNA as a CTC marker in different studies (Soeth et al, 2005; Zhou et al, 2011). The method of combined immunostaining for CD45, DAPI, and CEP8‐FISH has shown great potential for CTC detection; this method yielded sensitivities of 83.33% and 76.25% for detecting CTCs in lung and ovarian cancers, respectively (Ning et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…CTCs identified based on FISH‐CEP8 were associated with a curative effect following paclitaxel and cisplatin treatment in patients with advanced gastric cancer (Li et al, 2014). Patients with colon cancer who had CTCs detected by CK20 using real‐time PCR had substantially worse OS rates compared to those without detectable CTCs (Soeth et al, 2005). At the same time, several groups have shown that CTCs are not a prognostic factor for OS in several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the precise mechanisms of PDAC recurrence, but it occurs especially at the site of primary resection or in the liver (3,5). This implies that at the time of diagnosis, subclinical metastases or disseminated tumor cells are already present in many patients with no evidence of advanced disease (6) and might change their biological behavior upon surgical manipulation. In accordance with the latter, we recently observed a 3-fold increase in the number of liver and spleen metastases in an orthotopic xenotransplant animal model in mice after pancreatic tumor resection (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…2. The investigators conducted the Newcastle-Ottawa Scale (NOS) criteria to assess the methodological quality of the included studies [2][3][4][5][6][7][8][9][10]. They included the study by Uchikura K et al [10], which NOS scale was just 5.…”
Section: Dear Editormentioning
confidence: 99%